Anxiety, depressive symptoms, and cardiac autonomic function in perimenopausal and postmenopausal women with hot flashes: a brief report. Issue 12 (December 2018) - Fu, Polly; Gibson, Carolyn J.; Mendes, Wendy Berry; Schembri, Michael; Huang, Alison J.
Abstract: Objective: The aim of the study was to examine whether anxiety and depressive symptoms are associated with an adverse cardiac autonomic profile among midlife women with hot flashes. Methods: Anxiety and depressive symptoms were evaluated by validated self-administered questionnaires among peri- and postmenopausal women in a randomized trial of slow-paced respiration for hot flashes. Pre-ejection period (PEP), a marker of sympathetic activation, and respiratory sinus arrhythmia (RSA), a marker of parasympathetic activation, were measured at baseline and 12 weeks using impedance cardiography and electocardiography. Multivariable repeated measures linear regression models examined associations between anxiety and depression symptoms and autonomic markers, corrected for multiple comparisons with Benjamini–Hochberg procedure, and adjusted for age and body mass index. Results: Among the 121 participants, greater state anxiety was associated with shorter PEP, reflecting higher sympathetic activity ( β = −0.24, P = 0.02). Greater trait anxiety and cognitive anxiety were associated with lower RSA, reflecting decreased parasympathetic activity ( β = −0.03, P < 0.01 for Spielberger Trait Anxiety; β = −0.06, P = 0.02 for Hospital Anxiety and Depression Scale [HADS] Anxiety Subscale). Greater depressive symptoms were associated with lower RSA ( β = −0.06, P = 0.03 for HADS Depression Subscale; β = −0.03, P = 0.04 for Beck Depression Inventory). Conclusions: Among peri- and postmenopausal women with hot flashes, greater self-reported anxiety and depressive symptoms were associated with lower levels of resting cardiac parasympathetic activity, and greater state anxiety was associated with higher levels of cardiac sympathetic activity. Findings suggest that midlife women with increased anxiety and depressive symptoms may have an unfavorable cardiac autonomic profile with potential implications for their overall cardiovascular risk. Abstract : Supplemental Digital Content is available in the text